PENGARUH SISTEM DIGITAL DAN KEAMANAN ARSIP TERHADAP EFISIENSI WAKTU KERJA PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA DENPASAR - Dayu Junie (Universitas Warmadewa, 2017)
One of the step that Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar has taken to improve work time efficiency, have pay attention for influence of the factors amongs digital archives system and safety archives. The formulation of the problem in this research is whether digital archives system has the influence to work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar, whether safety archives the influence to work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar, whether digital archives system and safety archives in simultaneous has influence to work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar. Distination of this research is to know influence digital archives system toward work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar, to know influence safety archives toward work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar, to know influence digital archives system and safety archives in simultaneous toward work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar To solve the problems, the research conducted with the study sample of 35 employees at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar. The techniques of data collection through questionnaire. The analysis technique used is linier regression analysis. Based on the results obtained conclusions include there is positive and significant influence between digital archives system to work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar. There is positive and significant influence between safety archives to work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar. There are positive and significant influence between digital archives system and safety archives to work time efficiency at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar.